Clube de biologia para a promoção da alfabetização científica com abordagem investigativa: um guia de implementação - Wane Aparecida de Souza (2024)
The demand for comprehensive and civic education depends on scientific-technological education that empowers young people to transform themselves and society. Although the fulfillment of this request depends on knowledge of Biology, recent educational policies and reforms have devalued and emptied the teaching of this curricular component in high school. Faced with this reality, it is proposed to create Biology Clubs, inspired by Science Clubs, as a non-formal environment for the defense of Biology through the promotion of scientific literacy guided by research-based teaching. Therefore, given the need for more time and space dedicated to the scientific-biological training of students, this research aimed to study the processes of implementing a Biology Club and discuss its potential in promoting scientific literacy through an investigative approach focused on protagonism of club members. Since the implementation of a Biology Club requires a careful and consistent project, involving an educational institution, mediator and club members, bibliographical research resulted in the production of a guide, in e-book format, adaptable to the reality of the target audience, containing the essential guidelines, the theoretical and didactic foundations, the implementation stages and the documents necessary to contribute to solving the challenges and disseminating the clubs' initiative. The first half of the guide is dedicated to the club's identity and foundation in terms of objective and pedagogical methodology, while the second part focuses on the club's implementation, detailing the steps, structure, documents, mediator-club member interaction and instruments for monitoring the project and evaluating the club's intentions and results. Therefore, it is considered that the guide in e-book format will contribute to the dissemination of the Biology Clubs proposal, aiming at the dissemination of scientific literacy and the training of young protagonists.